Evaluation of Job Productivity Factors in the Hospitality Industry - MENDROFA, Cardinal Pranatal; HAREFA, Peringatan; GEA, Nov Elhan; LAIA, Otanius; HALAWA, Odaligoziduhu; BATE'E, Maria Magdalena (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.v12.6(54).07, 2021)
This research aims to analyze the evaluation of factors in job productivity of Hospitality industry employees in Nias District, Indonesia. This research using the sample of 110 respondent’s Hospitality industry employees in Nias District, Indonesia. Data which is obtained were analyzed by using “analysis of the path”. The result of research is the influence direct of discipline and significant on job satisfaction, discipline has an influential direct on job productivity, job promotion has an influential direct on job productivity, job satisfaction has an influential direct on job productivity, discipline has an influential direct on job productivity without through job satisfaction, and job promotion does not have an influential direct on job productivity through job satisfaction, and job promotion does not have an influential direct on job productivity through job satisfaction for Hospitality industry employees in Nias District, Indonesia.